2010
DOI: 10.3758/pbr.17.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to different mouth shapes influences visual perception of ambiguous lip speech

Abstract: 522Many studies have used visual adaptation to investigate whether recent visual experience influences face perception (e.g., Calder, Jenkins, Cassel, & Clifford, 2008;DeBruine, Jones, Unger, Little, & Feinberg, 2007;Little, DeBruine, & Jones, 2005;Rhodes, Jeffery, Watson, Clifford, & Nakayama, 2003;Webster, Kaping, Mizokami, & Duhamel, 2004;Webster & MacLin, 1999). For example, adaptation to faces with expanded feature spacing causes the feature spacing of unmanipulated faces to appear contracted, whereas ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Experiment 2 then demonstrates equivalency in results based on web-based and laboratory-based adaptation studies of this kind. We note that while individuals may intuitively feel that data collected in the absence of an experimenter may produce more variable results, there is growing evidence that adaptation effects seen under laboratory conditions are also seen in web-based studies (Jones et al, 2008, 2010). Our experiment here demonstrates that the same effect is seen in experiments 1 and 2 despite difference in recruitment, presence of experimenter, and variation in equipment.…”
Section: Discussionmentioning
confidence: 83%
“…Experiment 2 then demonstrates equivalency in results based on web-based and laboratory-based adaptation studies of this kind. We note that while individuals may intuitively feel that data collected in the absence of an experimenter may produce more variable results, there is growing evidence that adaptation effects seen under laboratory conditions are also seen in web-based studies (Jones et al, 2008, 2010). Our experiment here demonstrates that the same effect is seen in experiments 1 and 2 despite difference in recruitment, presence of experimenter, and variation in equipment.…”
Section: Discussionmentioning
confidence: 83%
“…For example, an undistorted face seems expanded after viewing a face with features compressed toward the midline. Besides distortion, FAEs have been observed for a number of natural facial properties including identity (Leopold et al, 2001), gender (Webster et al, 2004), age (Schweinberger et al, 2010), ethnicity (Webster et al, 2004) as well as more dynamic facial features such as emotional expression (Webster et al, 2004; Fox and Barton, 2007), eye-gaze direction (Jenkins et al, 2006; Seyama and Nagayama, 2006), and lip angle (Jones et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, other studies have found analogous asymmetric effects of expression or identity changes on face recognition and discrimination tasks (Schweinberger and Soukup, 1998; Schweinberger et al, 1999; Atkinson et al, 2005). (Conversely, there are also examples where changeable aspects of the face such as mouth shape can show aftereffects that show little dependence on identity (Jones et al, 2010). …”
Section: Introductionmentioning
confidence: 99%